Monitoring the coefficient of variation using EWMA charts. - Castagliola, Philippe
The coefficient of variation (CV) is a quality characteristic that has several applications in applied statistics and is receiving increasing attention in quality control. A few papers have proposed control charts that monitor this normalized measure of dispersion. This paper suggests a new method to monitor the CV by means of two one sided EWMA charts of the coefficient of variation squared y2. Tables are provided for the statistical properties of the EWMA y2 when the shift size is deterministic or unknown. An example illustrates the use of these charts on real data gathered from a metal sintering process.
Keywords: Average run length; Markov chain; Unknown shift size